Development of High Photosensitive Gold Nanorods/Zinc Oxide Photodetector - Lin, Chi-Shen; Lin , Wei-Chih (ELEKTRIKA- Journal of Electrical Engineering, 2021)
In this study, we present a development and fabrication of the plasmonic ultraviolet Gold nanorods (GNRs)/zinc oxide photodetector (ZnO PD) by using the micro-fabrication technique. The synthesis of GNRs is based on the seed-mediated method and the length and diameter of synthesized GNRs are approximate 13±2.3 nm and 50±6.4 nm. After decorating GNRs to the ZnO PD by using spin coating, the on/off ratio of ZnO PD is increased from 9.8 to 70. The enhancement mechanism is attributed to the formation of a local Schottky interface in the metal-semiconductor interface and the LSPR effect can generate the hot electrons and enhance the light scattering. Furthermore, the µ-PL is applied to separate analyse the optical properties of ZnO and GNRs/ZnO film. The near band emission is significantly enhanced, and the defect emission is also suppressed by decorating GNRs on the surface of the ZnO film. The experiment results indicate that decorated GNRs on the surface of ZnO can improve the performance of the ZnO PD. Therefore, GNRs material has a high protentional to improve the photosensitivity of the ZnO PD for photocatalysis and optoelectronic applications.